2009
DOI: 10.1111/j.1365-2249.2009.04000.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial antigen-induced T helper type 1 (Th1) and Th2 reactivity of peripheral blood mononuclear cells from diabetic and non-diabetic tuberculosis patients andMycobacterium bovisbacilli Calmette–Guérin (BCG)-vaccinated healthy subjects

Abstract: SummaryPatients with diabetes mellitus are more susceptible to tuberculosis (TB), and the clinical conditions of diabetic TB patients deteriorate faster than nondiabetic TB patients, but the immunological basis for this phenomenon is not understood clearly. Given the role of cell-mediated immunity (CMI) in providing protection against TB, we investigated whether CMI responses in diabetic TB patients are compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 51 publications
2
60
0
4
Order By: Relevance
“…Several early studies reported reduced proinflammatory cytokines in patients with diabetes after infection with Mycobacterium tuberculosis (3,4). Two studies, however, reported the elevation of helper T-cell type 1 (Th1) cytokines in tuberculosis-infected diabetic hosts; one was conducted in streptozocin-treated mice (5) and another in diabetic and nondiabetic patients with tuberculosis (6).…”
mentioning
confidence: 99%
“…Several early studies reported reduced proinflammatory cytokines in patients with diabetes after infection with Mycobacterium tuberculosis (3,4). Two studies, however, reported the elevation of helper T-cell type 1 (Th1) cytokines in tuberculosis-infected diabetic hosts; one was conducted in streptozocin-treated mice (5) and another in diabetic and nondiabetic patients with tuberculosis (6).…”
mentioning
confidence: 99%
“…Increased Th2 responses have been postulated to play a role in susceptibility to TB, as IL-4 and IL-13 can undermine Th1-mediated immunity and drive inappropriate alternative activation of macrophages [40,41]. Previous studies suggest that TB patients have higher Th2 cells [42] and diabetic TB patients susceptible to TB partially come from a higher Th2 bias [43]. The ratios of Th1 cells to Th2 cells were higher and the proportion of Th2 cells and ratios of Th2 cells to Th17 cells were lower in peripheral blood from PTB patients, suggesting that the dynamic balance of Th1, Th2 and Th17 cells may influence the outcome of M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that diabetic patients have compromised immunity, which makes them more susceptible to bacterial infections such as tuberculosis [12,13]. But still the molecular link between tuberculosis and diabetes is not clearly understood [14]. Our investigation was aimed to understand the molecular link between DM and TB.…”
Section: Introductionmentioning
confidence: 99%